Effects of Constructed Wetlands Plants on Phosphorus Removal from Domestic Wastewater in Gaborone, Botswana - Autlwetse, Baboloki; Kimwaga, Richard Joseph (Tanzania Journal of Engineering and Technology, 2022)
The United Nations, Sustainable Development Goal (SDG) Target 6.3. aims at "halving the proportion of untreated waste water and substantially increasing recycling and safe reuse globally" by 2030. To achieve this target, sustainable and context-specific wastewater treatment systems are urgently needed. Constructed wetlands (CW) is one of the wastewater treatment technological options available. CW have been widely accepted and acknowledged as simple, low cost, alternative and appropriate domestic wastewater treatment technology. CW were piloted by the Department of Water Affairs, Gaborone, Botswana to assess their treatment performance. Specifically, the study investigated the effects of CW plants on Phosphorus (P) removal from domestic wastewater. The first CW cell (CA) was a control which was filled with sand only, the second cell (CB) was planted with Typha Latifolia, the third (CC) with Cyperus Papyrus and the fourth (CD) with Phragmites Mauritianus. Each cell had a surface area of 100m2 and received a wastewater discharge of 4m3 /day. River sand with porosity of 0.44 and particle size diameter ranging from 2-7mm was used as plants growing media. Wastewater samples were analysed in accordance with Standard Methods for Examination of Water and Wastewater. The results showed that the P treatment performance efficiencies for CA, CB, CC, and CD were 93.6%, 97.4%, 98.1% and 98.4% respectively. Despite that there was CW plants contribution towards P removal from domestic wastewater, there was however no statistically significant performance difference (p>0.05) in P removal between the CW cells planted with different plant species. The mean effluent P concentrations from the different CW cells were; CA 0.62mg/l, CB 0.28mg/l, CC 0.19mg/l and CD 0.16mg/l. Thus, the mean P concentration from the effluent of C1 was above the Botswana Bureau of Standards Limits of 0.5mg/l. Hence the effluent was non-compliant with Botswana standards for the discharge of effluent into the environment. Key words: Plants effects, performance, phosphorus removal, type of plant, no statistically significance difference, constructed wetlands.